Liability and criminal justice management: Resolving dilemmas and meeting future challenges - Russell, Gregory D. (American journal of criminal justice, 1994)
To reduce liability, police executives rely heavily on hierarchically imposed rule adherence to control subordinates’ discretion. This management approach runs counter to current advice on how to “best manage” a public entity. This article develops an innovative approach to police management that reduces liability exposure while improving the management of the organization in keeping with contemporary notions of human resource development.